From Burdens to Brownie Points : From “Have To’s” to “Want To’s” to Combat Climate Change - Pearlman, Rob (World Bank, Washington, DC, 2012)
You don't have to be a psychologist to find yourself having to change or influence people's behavior. And that is a challenge, especially when the change involves costs in time, effort, and money and the potential benefit is not yet tangible. Though many of us intellectually understand the global discussions about climate change and sustainability, author frequently have difficulty changing own daily behavior, let alone influencing that of others. International Finance Corporation (IFC) team has learned a lot about this over the past seven years. Author have learned how to transform what he initially perceived as burdens of operating building more sustainably into real cost savings, environmental impact reductions, and reputational benefits for IFC by changing attitudes and behavior starting with own. These lessons are applicable to IFC's internal operations and to helping IFC's clients improve their sustainability performance.